Experimental oral candidiasis in wistar rat model - Mustafa Al-Ahmad, Basma Ezzat (2019)
The human oral cavity is a unique ecological niche because it is constantly bathed in saliva, a biological fluid with antifungal and antibacterial activity. In addition, the constant salivary flushing action mechanically inhibits the accumulation of microorganisms in various oral niches.